2016
DOI: 10.1002/jpln.201500545
|View full text |Cite
|
Sign up to set email alerts
|

Biochar‐compost substrates in short‐rotation coppice: Effects on soil and trees in a three‐year field experiment

Abstract: Both biochar and compost may improve carbon sequestration and soil fertility; hence, it has been recommended to use a mixture of both for sustainable land management. Here, we evaluated the effects of biochar–compost substrates on soil properties and plant growth in short rotation coppice plantations (SRC). For this purpose, we planted the tree species poplar, willow, and alder in a no‐till field experiment, each of them amended in triplicate with 0 (= control) or 30 Mg ha−1 compost or biochar–compost substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 46 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…These results are in agreement with a recent field study, showing positive growth effects on the second crop after soil application [60]. In addition, our results also showed that neutral effects of weathering depending on biochar feedstocks and/or soil type may occur [60,61]. Further studies would be needed to investigate the mechanisms controlling the variation of biochar-compost interactions on plant growth over time.…”
Section: Effect Of Weathered Amendments On Ryegrass Growthsupporting
confidence: 92%
“…These results are in agreement with a recent field study, showing positive growth effects on the second crop after soil application [60]. In addition, our results also showed that neutral effects of weathering depending on biochar feedstocks and/or soil type may occur [60,61]. Further studies would be needed to investigate the mechanisms controlling the variation of biochar-compost interactions on plant growth over time.…”
Section: Effect Of Weathered Amendments On Ryegrass Growthsupporting
confidence: 92%
“…BC did not enhance survival or growth of a Eucalyptus hybrid on degraded soils in southern Amazonia [35]. Compost and BC-compost mixes did not improve the performance of poplar, willow, and alder SRWCs [36]. As evidenced by presentations at a 2018 international SRWC conference [37], the biochar-fertilizer study reported here appears to be unique.…”
Section: Discussionmentioning
confidence: 68%
“…The main soil type was a Luvic Stagnosol (Episiltic) (IUSS Working Group WRB, 2015), with a silty-loam texture (63% silt, 23% clay, and 14% sand). 31 For set 3, soil particles <2 mm from a C3/C4 vegetation change experiment at the Terrestrial Observatory TERENO, Selhausen, Germany, were sampled in 2014 (0−30 cm soil depth). Soil had been continuously cropped with maize since 2012 (Zea mays L.).…”
Section: ■ Experimental Approachmentioning
confidence: 99%